Oxidative Desulfurization of Dibenzothiophene Using Dawson Type Heteropoly Compounds/Tantalum as Catalyst - Risfidian Mohadi; Lusi Teresia; Najma Annuria Fithri; Aldes Lesbani; Nurlisa Hidayati (Universitas Gadjah Mada, 2016)
Catalyst (NH4)6[b-P2W18O62]/Ta has been synthesized by simple wet impregnation at 30-40 °C under atmospheric conditions using Dawson type polyoxometalate (NH4)6[b-P2W18O62] and tantalum. The catalyst was characterized by FTIR spectrophotometer, XRD, SEM, and N2 adsorption desorption methods. FTIR spectrum of (NH4)6[b-P2W18O62]/Ta showed that Dawson type polyoxometalate (NH4)6[b-P2W18O62] and Ta was successfully impregnated which was indicated by vibration spectrum at wavenumber of 900-1100 cm-1 for polyoxometalate and 550 cm-1 for Ta. The surface area of the (NH4)6[b-P2W18O62]/Ta after impregnation was higher than (NH4)6[b-P2W18O62]•nH2O and its morphology was found to be uniform. The catalytic activity of (NH4)6[b-P2W18O62]/Ta toward desulfurization of dibenzothiophene was three times higher than the original catalyst of (NH4)6[b-P2W18O62]•nH2O without impregnation. The catalytic regeneration test of catalyst (NH4)6[b-P2W18O62]/Ta showed that the catalytic activity for first regeneration of catalyst has similar catalytic activity with the fresh catalyst without loss of catalytic activity indicated by almost similar percent conversion.